Population ecology of the endangered aquatic carnivorous macrophyte Aldrovanda vesiculosa at a naturalised site in North America - Cross, A.; Skates, L.; Adamec, L.; Hammond, C.; Sheridan, P.; Dixon, Kingsley (Blackwell Publishing Ltd, 2015)
Aldrovanda vesiculosa is an aquatic carnivorous plant native to nutrient impoverished wetland systems in Australia, Africa, Asia, and continental Europe that has declined dramatically throughout its native range in the last century. A strong reliance upon carnivory generally limits its occurrence to specific, nutrient-poor, island-like microhabitats. Remaining native populations are generally small and fragmented, and empirical population ecology data for the species arelacking. Developing an understanding of the constraints to growth, establishment and reproduction in A. vesiculosa is crucial to conservation of the species. In contrast with the decline of the species throughout its native range, a number of large A. vesiculosa populations have become naturalised in North America. This study examines the population ecology of A. vesiculosa at one of these naturalised sites and assesses the species' potential invasiveness in terms of its ecological characteristics. Transect and quadrat surveys were used to determine the response of morphology, fecundity and spatial distribution to putative biotic and environmental variables, with glasshouse trials and a bird feeding experiment employed to test the persistence of seeds in the seed bank and after transport in bird guts. Although A. vesiculosa is capable of becoming locally abundant (up to 1260 individuals m-2) in wetland areas where biotic and abiotic conditions are optimal, it appears to compete poorly with floating and emergent macrophytes and is limited predominantly to specific microhabitats. The ecological characteristics of A. vesiculosa suggest that it poses a low invasion risk. The species' growth and reproductive potential are highest in shallow areas harbouring loose vegetation assemblages, with over two thirds of all individuals recorded from water 10-50 cm in depth and in areas with <50% native macrophyte cover. Seeds are unlikely to play a significant role in seasonal persistence or dispersal, with poor floral success (c. 10%), few seeds produced, low seed viability (<50%) throughout the study area and no seeds recovered from the sediment seed bank or recovered from bird faeces following gut transport. The stenotopic ecology of A. vesiculosa, and the continuing decline of dystrophic freshwater wetlands globally, indicate that remaining natural populations are highly sensitive and are likely to decline rapidly without adequate management. In addition to wetland management at the catchment scale to mitigate processes such as eutrophication, future conservation and reintroduction initiatives for A. vesiculosa must focus particularly on the identification, maintenance and restoration of optimal shallow humic microsites harbouring loose, open assemblages of emergent and floating macrophytes.